Research of hepatoprotectoral activity of derivatives of 1,2,4-triazole-3-tione containing hydroxy(phenyl)methyl substituent in a fifth position - Rud, A. M.; Frolova, Yu. S. (My University, 2018)
Aim. is to test the first synthesized 1,2,4-triazole-3-thione derivatives containing a hydroxy(phenyl)methyl substituent in the fifth position under tetrachloromethane hepatitis.
Keywords: тези доповідей